Transformer les conceptions naïves à l'aide de clips vidéo. Analyser puis scénariser une vidéo aide les futurs ingénieurs à intégrer le système de pensée newtonien - Benoît Raucent; Christian Ritter; Jim Plumat; Pascale Corten-Gualtieri (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Most students in engineering programmes start their first university physics course with a system of beliefs and intuitions which are often inconsistent with the standard Newtonian framework. This paper presents an experiment in collaborative learning with small teams aiming at helping students to relinquish their naïve intuitions about dynamics. An important aspect of this experiment is that students were asked to both critically analyze the contents of video clips illustrating mechanical dynamics and design and realize their own video clip. The efficacy of the activity was assessed. The success of the experiment is attributed to the choice of video clips clearly belonging to student culture, to the students working in teams, and to the quality of the tutoring.